2002
DOI: 10.1200/jco.2002.07.075
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Study to Evaluate the Use of High-Dose Therapy as Part of Primary Treatment for “Aggressive” Lymphoma

Abstract: Results of the randomized trial comparing CHOP-like chemotherapy with early HDT do not support the use of HDT with carmustine, etoposide, cytarabine, and melphalan following shortened standard chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 17 publications
5
54
0
4
Order By: Relevance
“…9 Although this study is not a concurrent comparison of treatment options and any conclusions between nonrandomized groups may be subject to differences in observed and unobserved prognostic factors, it is unlikely that the differences in outcome seen in control and auto-SCT groups are caused by factors other than treatment. While both negative and positive impact of upfront HDT and auto-SCT on survival have been reported, [20][21][22][23][24] our findings are in line with positive studies, which suggested that especially young high-risk patients benefit from upfront HDT. 21,24 The finding showing that the benefit of HDT and auto-SCT is only seen in the non-GC subgroup is also important as it highlights the fact that two phenotypes are biologically and clinically distinct.…”
Section: Discussionsupporting
confidence: 81%
“…9 Although this study is not a concurrent comparison of treatment options and any conclusions between nonrandomized groups may be subject to differences in observed and unobserved prognostic factors, it is unlikely that the differences in outcome seen in control and auto-SCT groups are caused by factors other than treatment. While both negative and positive impact of upfront HDT and auto-SCT on survival have been reported, [20][21][22][23][24] our findings are in line with positive studies, which suggested that especially young high-risk patients benefit from upfront HDT. 21,24 The finding showing that the benefit of HDT and auto-SCT is only seen in the non-GC subgroup is also important as it highlights the fact that two phenotypes are biologically and clinically distinct.…”
Section: Discussionsupporting
confidence: 81%
“…14 Some studies, in particular, have shown little or no benefit from up-front dose intensification. [15][16][17][18] Risk-adapted therapy may be performed after patient stratification according to International Prognostic Index (IPI) score 19 or, as demonstrated recently, by applying a standardized and widely acknowledged molecular or immunohistochemical profiling, particularly in a high-grade lymphoma setting. [20][21][22][23] Although the IPI score represents the most reliable prognostic index in aggressive lymphomas, patients belonging to the same IPI prognostic group may show significantly different outcomes, primarily because diffuse large B-cell lymphoma (DLBCL) tends to behave heterogeneously.…”
mentioning
confidence: 99%
“…Clinical treatment protocols in high-income countries are based on the FAB LMB study or the Berlin-Frankfurt-Muenster protocols and achieve outstanding overall survival rates in children (3). Nevertheless, there are cases of poor clinical outcome caused by the toxicity of the intensive chemotherapy, tumor lysis syndrome, or metastatic spread of lymphoma cells to the central nervous system (4)(5)(6)(7). Especially elderly and HIV-positive patients show a poorer overall survival rate because of treatment-related mortality (3,8,9).…”
Section: Introductionmentioning
confidence: 99%